Evaluation of juveniles' competence to stand trial - Kruh, Ivan Peter (Best practices in forensic mental health assessment, 2009)
The legal context -- Forensic mental health concepts -- Empirical foundations and limits -- Application -- Preparation for the evaluation -- Data collection -- Interpretation -- Report writing and testimony